2007
DOI: 10.1177/154405910708601117
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Bone Density and Periodontal Disease in Men

Abstract: Bone loss is a feature of both periodontitis and osteoporosis, and periodontal destruction may be influenced by systemic bone loss. This study evaluated the association between periodontal disease and bone mineral density (BMD) in a cohort of 1347 (137 edentulous) older men followed for an average of 2.7 years. Participants were recruited from the Osteoporotic Fractures in Men Study. Random half-mouth dental measures included clinical attachment loss (CAL), pocket depth (PD), calculus, plaque, and bleeding. BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 17 publications
3
58
2
1
Order By: Relevance
“…6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession. 18 With the exception of Phipps et al 17 , the results of other longitudinal studies regarding the relationship between systemic BMD and periodontal disease progression support this finding. 19,20 These studies suggest that systemic bone loss arising from uncoupled bone remodelling due to oestrogen deficiency also affects the jawbone and is important for the progression of bone loss in periodontitis.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession. 18 With the exception of Phipps et al 17 , the results of other longitudinal studies regarding the relationship between systemic BMD and periodontal disease progression support this finding. 19,20 These studies suggest that systemic bone loss arising from uncoupled bone remodelling due to oestrogen deficiency also affects the jawbone and is important for the progression of bone loss in periodontitis.…”
Section: Discussionsupporting
confidence: 76%
“…30 The association between systemic BMD and periodontal disease has been addressed in a number of studies. 6,[9][10][11][12][13][14][15][16][17][18][19][20] While the cross-sectional studies conducted on post-menopausal osteoporotic females and elderly males suggested that there was a correlation between systemic BMD and periodontal disease, [9][10][11]14,35 other studies conducted on pre-menopausal females and young male populations did not support such a relationship. 6,12,13 A recent longitudinal study conducted on elderly Chinese males suggested that osteoporosis is associated with severe loss of clinical attachment and interproximal gingival recession.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the present study, we identified that specifically older men with periodontitis were at risk for fractures. This differs from the perception of a lack of association between periodontitis and osteoporosis in men [26].…”
Section: Accepted M Manuscriptcontrasting
confidence: 47%
“…The risk for osteoporosis is generally believed to be higher in women. Studies have failed to confirm an association between osteoporosis and periodontitis in older men [26]. This may, in part, be the result of a high degree of undiagnosed osteoporosis in older men.…”
Section: Introductionmentioning
confidence: 86%